Distinct roles for the RNA-binding protein Staufen1 in prostate cancer - Marcellus, Kristen A; Crawford Parks, Tara E; Almasi, Shekoufeh; Jasmin, Bernard J (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Prostate cancer is one of the most common malignant cancers with the second highest global rate of mortality in men. During the early stages of disease progression, tumour growth is local and androgen-dependent. Despite treatment, a large percentage of patients develop androgen-independent prostate cancer, which often results in metastases, a leading cause of mortality in these patients. Our previous work on the RNA-binding protein Staufen1 demonstrated its novel role in cancer biology, and in particular rhabdomyosarcoma tumorigenesis. To build upon this work, we have focused on the role of Staufen1 in other forms of cancer and describe here the novel and differential roles of Staufen1 in prostate cancer. Methods Using a cell-based approach, three independent prostate cancer cell lines with different characteristics were used to evaluate the expression of Staufen1 in human prostate cancer relative to control prostate cells. The functional impact of Staufen1 on several key oncogenic features of prostate cancer cells including proliferation, apoptosis, migration and invasion were systematically investigated. Results We show that Staufen1 levels are increased in all human prostate cancer cells examined in comparison to normal prostate epithelial cells. Furthermore, Staufen1 differentially regulates growth, migration, and invasion in the various prostate cancer cells assessed. In LNCaP prostate cancer cells, Staufen1 regulates cell proliferation through mTOR activation. Conversely, Staufen1 regulates migration and invasion of the highly invasive, bone metastatic-derived, PC3 prostate cells via the activation of focal adhesion kinase. Conclusions Collectively, these results show that Staufen1 has a direct impact in prostate cancer development and further demonstrate that its functions vary amongst the prostate cancer cell types. Accordingly, Staufen1 represents a novel target for the development of much-needed therapeutic strategies for prostate cancer.